Coronacoccus hengyangensis gen. et sp. nov., a new member of Chlorellaceae (Trebouxiophyceae, Chlorophyta) with radiococcacean morphology. Issue 4 (1st July 2018) - Song, Huiyin; Liu, Xudong; Hu, Yuxin; Wang, Qinghua; Long, Jijian; Liu, Guoxiang; Hu, Zhengyu
Abstract: The Chlorellaceae is a family in the order Chlorellales that includes mostly coccoid algae of minute sizes, and a portion of this family was separated into two sister groups (the Chlorella clade and the Parachlorella clade) according to molecular phylogenetic analyses. To date, the Parachlorella clade comprises 11 genera that exhibit a range of morphological variation. In this study, we discovered from China a strain marked as FACHB-2137; we use a polyphasic approach, including phylogenetic analyses of SSU+ITS rDNA, an ITS2/CBC (compensatory base changes) approach, light microscopy and transmission electron microscopy, to characterise the strain. Molecular analyses revealed that the strain was nested within the Parachlorella clade (Chlorellaceae, Trebouxiophyceae), forming an independent lineage separated from other genera. The new strain's morphology has the characteristic autospores that release by rupturing or splitting of the cell wall into several (two to four) portions; this strain differs from other members of the Parachlorella clade in that the mother cell wall remains rather distinct, and the daughter cells remain as cup-shaped in the colonial mucilage for an extended period. Morphologically, this new strain closely resembles members of the Radiococcaceae. This indicates that inferring family-level relationships based exclusively on morphology can be problematic. We describe this alga as a new genus and species, Coronacoccus hengyangensis gen. et sp. nov . This morphotype is described for the first time in the Parachlorella clade.